Analysis of Regional Minimum Wage Regulation and It's Implementation: A Case Study of A Multinational Company - Adelia Azzahra; Ade Fitria Fatimah; Kofi Agyenim Boateng; Mohamad Maulana Ridzki (Green Publisher Indonesia, 2024)
This study examines the compliance of multinational companies with the Regional Minimum Wage (UMR) regulations in Indonesia and the factors contributing to violations. Although UMR is designed to protect workers' welfare, many companies still pay below the established standards. A qualitative research method was employed to collect data through in-depth interviews, field observations, and document analysis. The findings reveal that UMR violations occur across various industrial sectors, with violation rates ranging from 10% to 20%. Factors contributing to these violations include a lack of oversight, ineffective law enforcement, and legal uncertainties related to regulations that vary between regions. The research also identifies that UMR violations significantly impact workers' welfare, including difficulties in meeting basic needs and increased stress due to financial uncertainty. To enhance compliance, the study recommends improving oversight and law enforcement, harmonizing UMR standards across regions, and developing an anonymous complaint system for workers. These findings are expected to provide insights for policymakers, company management, and workers to improve the implementation of UMR regulations and enhance workers' welfare in Indonesia.